CHANGES IN PLATELET AGGREGATION AND NIHSS AFTER ANTI-PLATELET THERAPY FOR ACUTE ISCHEMIC STROKE PATIENTS AT H. ADAM MALIK GENERAL HOSPITAL MEDAN - Novi Apriani, Puji Pinta O. Sinurat & Alfansuri Kadri (International Journal of Research Science and Management, 2020)
Background: Acute ischemic stroke is caused by blockage of the cerebral arteries due to thrombus originating from excessive clotting of platelets. Increased platelet activity impacts the risk of atherothrombosis. The clinical impact of this blockage can be seen in changes in platelet aggregation and NIHSS after anti-platelet administration. Objectives: This study aims to determine changes in platelet aggregation and NIHSS after administration of antiplatelet therapy in acute ischemic stroke patients. Methods: This study was a Quasi Experimental Study with the method of Pre and Post-test Only Group selected by consecutive non-random sampling technique, in which patients diagnosed with ischemic stroke treated at H Adam Malik General Hospital Medan. The study began from March to July 2020. Results: The study was conducted on 38 samples consisting of 18 men and 20 women with an average age of 58.92(±7.539) years. There was a significant change between platelet aggregation and NIHSS (p<0.001). There was a significant relationship between platelet aggregation with NIHSS the first day before the administration of anti platelets (p=0.018) and correlation test (r=0.339) positive direction (unidirectional). There was no significant relationship between platelet aggregation with NIHSS in the seventh day after anti platelet administration (p=0.394). Conclusions: There were significant changes between platelet aggregation and NIHSS scores. There was a significant relationship between platelet aggregation and NIHSS the first day before anti platelet administration. There was no significant relationship between platelet aggregation and NIHSS in the seventh day after anti platelet administration.